2022
DOI: 10.1007/s10896-022-00413-6
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Relationships between Couples to Respond to Domestic Violence: a Commentary on Policy Changes Needed to Support this Evolution

Abstract: Broad calls to narrow the role of police in American society have begun to include arguments to reduce the carceral responding to intimate partner violence (IPV) and add a stronger social response. The field’s improved understanding of lethality risk assessment; better classification of offender risk by past involvement with general violence or family only violence; and positive findings from trials of relationship strengthening interventions as couples counseling, restorative justice practices, and mediation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Furthermore, they are consistent with the results of Zemp et al (2017), who found that couple coping reinforcement training is suitable for couples to deal with life issues, encouraging the application of positive behaviors (Zemp et al, 2017). These findings also align with further previous studies (Barkat, 2002;Barth & Jiranek, 2023;Isanejad & Alizade, 2020;Mahapatro & Singh, 2020;Rahimi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, they are consistent with the results of Zemp et al (2017), who found that couple coping reinforcement training is suitable for couples to deal with life issues, encouraging the application of positive behaviors (Zemp et al, 2017). These findings also align with further previous studies (Barkat, 2002;Barth & Jiranek, 2023;Isanejad & Alizade, 2020;Mahapatro & Singh, 2020;Rahimi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…However, couples may engage in harmful relationships, such as severe conflicts or violence, which can seriously jeopardize the mental health of the family and the relationships among its members. Violence is defined as a behavioral pattern imposed through the creation of fear, threat, and harassing behaviors to exert power and control over another person (Barth & Jiranek, 2023;Jahani Janaghard, 1399). Moreover, the most common form of violence within the family is "domestic violence," also referred to as violence against women or intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…The area of crime cessation is complicated by additional considerations: The need to take responsibility for one's own actions is a cornerstone of the criminal law and the entire criminal justice apparatus. Those involved in the system generally have only the individual to work with, and there are practical and ethical difficulties in attempting to incorporate families and partners much less peers into programmatic emphases. For example, some federal and state regulations prohibit or discourage the use of couple‐based programs in connection with intimate partner violence (IPV) (Barth & Jiranek, 2022). Many of those who work within the criminal justice system have been trained in psychology or related disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Those involved in the system generally have only the individual to work with, and there are practical and ethical difficulties in attempting to incorporate families and partners much less peers into programmatic emphases. For example, some federal and state regulations prohibit or discourage the use of couple‐based programs in connection with intimate partner violence (IPV) (Barth & Jiranek, 2022 ).…”
Section: Introductionmentioning
confidence: 99%